2022
DOI: 10.1136/bmjopen-2021-060281
|View full text |Cite
|
Sign up to set email alerts
|

Strengthening the clinical academic pathway: a systematic review of interventions to support clinical academic careers for doctors and dentists

Abstract: ObjectiveEvaluate existing evidence on interventions intended to increase recruitment, retention and career progression within clinical academic (CA) careers, including a focus on addressing inequalities.DesignSystematic review.Data sourcesMedline, Embase, Cochrane Controlled Register of Trials, PsycINFO and Education Resource Information Center searched October 2019.Study selectionEligible studies included qualified doctors, dentists and/or those with a supervisory role. Outcomes were defined by studies and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“… 10 11 A recent systematic review of the existing interventions to support CA careers for doctors and dentists found that protected research time could enhance CA retention and career progression. 11 In addition, to bolster the feeling of belonging for minoritised CAs, representation and inclusion is crucial.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 10 11 A recent systematic review of the existing interventions to support CA careers for doctors and dentists found that protected research time could enhance CA retention and career progression. 11 In addition, to bolster the feeling of belonging for minoritised CAs, representation and inclusion is crucial.…”
Section: Discussionmentioning
confidence: 99%
“…7 8 Various challenges have already been recognised for CAs, such as limited funding, financial insecurity, limited CA positions and the demanding workload of a clinical role. [9][10][11][12][13] For CAs from minoritised backgrounds, those challenges could be compounded. For example, for female CAs, social expectations around family commitment and parenting responsibilities could result in their being unable to pursue CA careers.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
See 1 more Smart Citation
“…As highlighted by previous studies, these multifaceted future interventions including those intended to address inequities, require careful evaluation to determine their usefulness. [25][26][27] Additionally the involvement of junior academic staff and staff with protected characteristics in co-developing the evaluation of these future interventions is vital.…”
Section: Discussionmentioning
confidence: 99%
“…An international body of literature has developed highlighting concerns around the future supply of clinical academics in the healthcare system,1–9 and issues around clinical academic progression to early stage postdoctoral level,10 11 including studies addressing gender difference in career progression 7 12–15. Thus, a need to undertake an evaluation of the CL and its role in addressing the gap around clinical academic progression from early to late postdoctoral level was identified.…”
Section: Introduction/rationalementioning
confidence: 99%